Acute Alithiasic Cholecystitis and Human Herpes Virus Type-6 Infection: First Case - Maria Miguel Gomes; Henedina Antunes; Ana Luísa Lobo; Fernando Branca; Jorge Correia-Pinto; João Moreira-Pinto (Case Reports in Pediatrics)
A three-year-old male child presented with erythematous maculopapular nonpruritic generalized rash, poor feeding, vomiting, and cramping generalized abdominal pain. He was previously healthy and there was no family history of immunologic or other diseases. On examination he was afebrile, hemodynamically stable, with painful palpation of the right upper quadrant and positive Murphy’s sign. Laboratory tests revealed elevated inflammatory markers, elevated aminotransferase activity, and features of cholestasis. Abdominal ultrasound showed gallbladder wall thickening of 8 mm with a positive sonographic Murphy’s sign, without gallstones or pericholecystic fluid. Acute Alithiasic Cholecystitis (AAC) was diagnosed. Tests for underlying infectious causes were negative except positive blood specimen for Human Herpes Virus Type-6 (HHV-6) by polymerase chain reaction. With supportive therapy the child became progressively less symptomatic with gradual improvement. The child was discharged on the sixth day, asymptomatic and with improved analytic values. Two months later he had IgM negative and IgG positive antibodies (1/160) for HHV-6, which confirmed the diagnosis of previous infection. In a six-month follow-up period he remains asymptomatic. To the best of our knowledge, this represents the first case of AAC associated with HHV-6 infection.